Adaptability and phenotypic stability of sugarcane clones - Vilas Boas Regis, Jiuli Ani [UNESP]; Costa Andrade, Joao Antonio da [UNESP]; Santos, Adriano dos; Moraes, Aparecido; Romo Trindade, Rafael William [UNESP]; Ribeiro Henriques, Hermano Jose [UNESP]; Polis, Bruno Henrique; Oliveira, Luiz Carlos (Empresa Brasil Pesq Agropec, 2018)
The objective of this work was to select superior sugarcane (Saccharum officinarum) clones with good stability and adaptability, considering the genotype x environment interaction in two productive cycles. Twenty-five early clones plus five control clones were evaluated during two cuts (ratoon cane and plant cane) in 24 environments. A randomized complete block design was used, with three replicates. Tons of stems per hectare and tons of pol per hectare were evaluated. To verify adaptability and stability, the bisegmented regression and the multivariate (AMMI and GGE biplot) methods were used. According to the three methods, which are complementary regarding the desired information, the most promising clones in terms of stability and general adaptability are G5, G12, and G13; the last two are closest to the ideal genotype. The G13 clone is highly productive in favorable and unfavorable environments, presenting the highest averages for ton of stems and pol per hectare. The G3, G4, G10, G15, G17, G18, G22, G23, G25, G26, and G30 clones are not recommended for the 24 evaluated environments.
Keywords: Saccharum officinarum; AMMI; genotype x environment interaction; GGE biplot